Tipping the scales: Immunotherapeutic strategies that disrupt immunosuppression and promote immune activation - Santiago-Sánchez, Ginette S.; Hodge, James W.; Fabian, Kellsye P. (Frontiers in Immunology, 2022)
Immunotherapy has emerged as an effective therapeutic approach for several cancer types. However, only a subset of patients exhibits a durable response due in part to immunosuppressive mechanisms that allow tumor cells to evade destruction by immune cells. One of the hallmarks of immune suppression is the paucity of tumor-infiltrating lymphocytes (TILs), characterized by low numbers of effector CD4+ and CD8+ T cells in the tumor microenvironment (TME). Additionally, the proper activation and function of lymphocytes that successfully infiltrate the tumor are hampered by the lack of co-stimulatory molecules and the increase in inhibitory factors. These contribute to the imbalance of effector functions by natural killer (NK) and T cells and the immunosuppressive functions by myeloid-derived suppressor cells (MDCS) and regulatory T cells (Tregs) in the TME, resulting in a dysfunctional anti-tumor immune response. Therefore, therapeutic regimens that elicit immune responses and reverse immune dysfunction are required to counter immune suppression in the TME and allow for the re-establishment of proper immune surveillance. Immuno-oncology (IO) agents, such as immune checkpoint blockade and TGF-β trapping molecules, have been developed to decrease or block suppressive factors to enable the activity of effector cells in the TME. Therapeutic agents that target immunosuppressive cells, either by direct lysis or altering their functions, have also been demonstrated to decrease the barrier to effective immune response. Other therapies, such as tumor antigen-specific vaccines and immunocytokines, have been shown to activate and improve the recruitment of CD4+ and CD8+ T cells to the tumor, resulting in improved T effector to Treg ratio. The preclinical data on these diverse IO agents has led to the development of ongoing phase I and II clinical trials. This review aims to provide an overview of select therapeutic strategies that tip the balance from immunosuppression to immune activity in the TME.